Endoscopic Repair of Gastrocolic and Colocutaneous Fistulas Complicating Percutaneous Endoscopic Gastrostomy Tube. (11th February 2020) - Chime, Chukwunonso; Baiomi, Ahmed; Kumar, Kishore; Patel, Harish; Dev, Anil; Makker, Jasbir
Abstract : Percutaneous endoscopic gastrostomy (PEG) tube feeding has become one of the options for supplemental feeding in a selected group of patients. It is a generally safe procedure usually undertaken by a gastroenterologist or a surgeon in most cases but with over 200, 000 tubes being placed yearly, there is bound to be complications. Some of the encountered complications include bleeding, site infection, tube migration, and inadvertent creation of fistula. We present our index patient admitted from a long-term care facility for feculent vomiting and fecal material through the PEG tube. Imaging and colonoscopy confirmed the presence of both a gastrocolic and a colocutaneous fistula, both closed endoscopically with an over-the-scope and through-the-scope clips, respectively. Feeding through a nasogastric tube was resumed after 48 hours, and by the second week of admission, the patient was discharged back to the facility after placement of a new PEG tube.